The Seasonal Behavior of the Characteristic Wave in Low Latitudes - Kurt, Kadri (My University, 2021)
This study aims to investigate the magnitude of polarization of characteristic wave (Dz=0), for all seasons by using the real geometry of\rthe Earth’s magnetic field for the selected altitudes (390, 410, 450, 500, 550 and 600 Km) in the equatorial anomaly region at low latitudes\r(-300S and 300N). The part of imaginary of the characteristic wave having a complex structure in latitudes where equatorial anomaly occurs\rit has a dramatically resemblance to the change of electron density, and the real part has been similarity showing with the change with\rlatitude of the refractive index for all seasons for 12.00-24.00LT.
Keywords: Equatorial Anomaly; Ionosphere; Characteristic wave